Peningkatan Kualitas Prasarana dengan Redesain Sekolah Dasar Muhammadiyah Mrisi, Bantul, Menggunakan Software SAP 2000 dan SketchUp - Emil Adly; Anita Rahmawati; Wahyu Widodo; Yoga Aprianto H; Laras Astuti (Universitas Muhammadiyah Semarang, 2021)
The main factor for the success of the implementation of education in schools is the infrastructure in the form of completeness of facilities that become the benchmark in all learning activities. To produce students who have comprehensive knowledge must be supported by facilities and skilled teaching staff. Muhammadiyah Elementary School of Mrisi still needs attention in terms of educational infrastructure facilities that are still lacking with a relatively small number of students. The purpose of this community service is to redesign the buildings, rooms, and the design of school facilities. The initial method used is a survey by measuring and calculating the area of buildings, columns, beams and assessing the existing physical condition and then developing it according to the available land, then it will be simulated using SAP 2000 software, 3D drawings using SketchUp, and calculating the budget plan. The result of the design is a two-level school building with larger beam and column sizes as well as a sturdy and earthquake-resistant structure. Furthermore, several redesigns of facilities such as warehouses, prayer rooms, and first-level classrooms, toilets, canteens, became cleaner and more attractive. The second level is designed for additional classrooms, halls, laboratories, libraries. Other supporting facilities in the form of guard posts, gates, parking lots become more attractive. With a planned budget of Rp 6,226,839,700. -, the school can raise funds to develop school facilities in accordance with the designs that have been made and mutually agreed upon.